Inspiring active learning : a handbook for teachers - Harmin, Merrill (Alexandria, Va. : Association for Supervision and Curriculum Development, 1994)
A revised and greatly expanded 2nd edition featuring more than 250 research based and teacher tested strategies for solving teaching problems and transforming classrooms into communities of active, responsible learners.
Includes bibliographical references.
Keywords: Teaching -- Handbooks, manuals, etc; Motivation in education -- Handbooks, manuals, etc; Active learning -- Handbooks, manuals, etc